A giant abdominal well differentiated Liposarcoma: A rare etiology of abdominal mass - Soukaina EL Yazal; Abdelouahed Louzi; Fatima Z Lairani; Soukaina Jiddi; Imane Haraki; Sofi a Oubaha; Zouhour Samlani Sebbane; Khadija Krati (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2018)
Liposarcoma is the most common retroperitoneal sarcoma and represents more than 15% of all sarcomas. Well differentiated liposarcoma is usually located in the extremities. We report the case of a patient with a giant retroperitoneal liposarcoma revealed by an abdominal mass. Case presentation: A 67 years old woman is admitted to our hospital for abdominal distension and pain that has been evolving for 2 years. Medical examination revealed a huge abdominal mass. Computed tomography (CT) scan showed a giant retroperitoneal mass with regular borders, pressing back abdominal organs and encasing the right kidney evoking a very probable liposarcoma. The patient has thus undergone a surgical resection of the mass alongside with nephrectomy of the right kidney. Histological fi ndings confi rmed well differentiated liposarcoma. Postoperative follow up was simple and no recurrent tumor was identifi ed. The only known effective treatment of well differentiated iposarcoma is the complete surgical resection.